E-HeaRT BPA: electronic health record telemetry BPA. Issue 1139 (28th May 2020) - Chin, Kuo-Kai; Svec, David; Leung, Benjamin; Sharp, Christopher; Shieh, Lisa
Abstract: Introduction: Continuous cardiac monitoring in non-critical care settings is expensive and overutilised. As such, it is an important target of hospital interventions to establish cost-effective, high-quality care. Since inappropriate telemetry use was persistently elevated at our institution, we devised an electronic best practice alert (BPA) and tested it in a randomised controlled fashion. Methods: Between 4 March 2018 and 5 July 2018 at our 600-bed academic hospital, all non-critical care patients who had at least one telemetry order were randomised to the control or intervention group. The intervention group received daily BPAs if telemetry was active. Results: 275 and 283 patients were randomised to the intervention and control groups, respectively. The intervention group triggered 1042 alerts and trended toward fewer telemetry days (3.8 vs 5.0, p=0.017). The intervention group stopped telemetry 31.7% of the alerted patient-days compared with 23.3% for the control group (OR 1.53, 95% CI 1.24 to 1.88, p<0.001). There were no significant differences in length of stay, rapid responses, code blues, or mortality between the two groups. Conclusions: Using a randomised controlled design, we show that BPAs significantly reduce telemetry without negatively affecting patient outcomes. They should have a role in promoting high-value telemetry use.